PENERAPAN MODEL CIRC UNTUK MENINGKATAN HASIL BELAJAR BAHASA INDONESIA TEMA PERISTIWA DALAM KEHIDUPAN PADA SISWA KELAS V SDN TAMBAKREJO TAHUN AJARAN 2019/2020 - Solikhatun Diniah; Ngatman Ngatman; Ratna Hidayah (Universitas Sebelas Maret, 2020)
The study aimed: (1) to describe the steps in implementing the CIRC model, (2) to improve Indonesian language learning outcomes through the application of the CIRC model, and (3) to describe the obstacles and solutions in implementing the CIRC model in improving Indonesian language learning outcomes. It was collaborative classroom action research conducted in two cycles. The subjects were teacher and students of fifth grade of SDN Tambakrejo. Data collection techniques were observation, interviews, and tests. Data analysis were data reduction, data presentation, and drawing conclusion. The results showed that: (1) the steps to the application of Cooperative Integrated Reading and Composition (CIRC) model were: a) having orientation, b) forming group, c) distributing texts, d) having discussion, e) having presentation, f) drawing conclusions, and g) closing. (2) The application of CIRC model improved student Indonesian learning outcomes. The averages of student mastery in Indonesian language learning outcomes were 66.07% in cycle I and 85.71% in cycle II. (3) The obstacles were: the students were passive in asking questions, answering questions, and giving opinions. The solutions to overcome the obstacles were the teacher guided, motivated, and gave reward to students giving opinions and answering questions so that the students had courage to give opinions in front of the class. It concludes that the application of Cooperative Integrated Reading and Composition (CIRC) model improves Indonesian language learning outcomes to fifth grade students of SDN Tambakrejo in academic year of 2019/2020.